(3CfHGA fLHGA GdCHfGAs - (3eMeO Hf YHO Gddg CHj eMeO Hf eMeO Hf nXnaQ GdUbdj Gdecqj, CHh YHO Gddg, MLI GdOjf,J (B565 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdCeGe Gdeci UGf Gddg bOQg GdMeO ddg GdeMehO MH GdTghGJ ef GdfGQ hGdfjf s
(3BNQgG (B:s
(3ai MGdg UHGi aCSJLjH Cf CPcQ QHi HGddSGf bdJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B241s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B595 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B34 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs